Estrategias de e-marketing para posicionar los servicios del Hotel Palacio Real en la ciudad de Guaranda, provincia bolívar. Año 2022 - Pujos Pilco, Ana Lucia (2023)
This research was conducted with the objective of designing marketing strategies to position the services of the Palacio Real Hotel, providing the design of clear and concise marketing strategies to publicize the services offered by the hotel. The methodology was of qualitative approach because the data collection was carried out without numerical measurement, which allowed us to investigate and interview the hotel staff, since they are the ones in charge of offering a good service to their customers. And the results that were presented show that at present the hotel has been economically affected by the post-pandemic of Covid-19 and also the decrease of the personnel. On the other hand, it is evident the lack of organizational and functional structure that allows decision making towards the fulfillment of objectives and a good evolution and competitiveness in the hotel sector. Likewise, the demand of the people who visit the hotel for work or leisure reasons, depending on the season, was known. Within the supply, it was observed that in the hotel sector, according to the tourism cadastre for the year 2022, there are 9 two-star hotels and the Palacio Real hotel has 3 stars. Finally, in the design of the marketing strategies, we worked with the SWOT matrix where we obtained as a result the low positioning of the hotel caused by the lack of advertising. Keywords: Marketing strategies, Hotel, Demand, Organizational structure.